2021
DOI: 10.1038/s41598-021-82449-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial associations in the healthy human gut microbiome across populations

Abstract: In a microbial community, associations between constituent members play an important role in determining the overall structure and function of the community. The human gut microbiome is believed to play an integral role in host health and disease. To understand the nature of bacterial associations at the species level in healthy human gut microbiomes, we analyzed previously published collections of whole-genome shotgun sequence data, totaling over 1.6 Tbp, generated from 606 fecal samples obtained from four di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 90 publications
3
44
0
Order By: Relevance
“…Bacterial genome relative abundances in each sample were estimated using a probabilistic framework based on a mixture model. The framework utilized an Expectation-Maximization (EM) algorithm to perform soft assignment of the reads to the reference genomes and was found to be highly accurate ( Xia et al, 2011 ; Loftus et al, 2021 ). We have previously demonstrated that samples with less than 250,000 mapped reads display diminished accuracy for taxonomic profiling, consequently all samples that contained less than 250,000 mapped reads threshold were not used for downstream analysis ( Loftus et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bacterial genome relative abundances in each sample were estimated using a probabilistic framework based on a mixture model. The framework utilized an Expectation-Maximization (EM) algorithm to perform soft assignment of the reads to the reference genomes and was found to be highly accurate ( Xia et al, 2011 ; Loftus et al, 2021 ). We have previously demonstrated that samples with less than 250,000 mapped reads display diminished accuracy for taxonomic profiling, consequently all samples that contained less than 250,000 mapped reads threshold were not used for downstream analysis ( Loftus et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The framework utilized an Expectation-Maximization (EM) algorithm to perform soft assignment of the reads to the reference genomes and was found to be highly accurate ( Xia et al, 2011 ; Loftus et al, 2021 ). We have previously demonstrated that samples with less than 250,000 mapped reads display diminished accuracy for taxonomic profiling, consequently all samples that contained less than 250,000 mapped reads threshold were not used for downstream analysis ( Loftus et al, 2021 ). When calculating relative abundances, any value below 1 × 10 –5 was considered statistical noise (and set to 0).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations